2019
DOI: 10.1186/s13075-019-1817-y
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and perceived risk of cardiovascular disease among individuals living with rheumatoid arthritis is low: results of a systematic literature review

Abstract: BackgroundIndividuals with rheumatoid arthritis (RA) are at risk of developing cardiovascular disease (CVD), but patient perceptions of CVD are not routinely assessed. We performed a systematic literature review to evaluate awareness of the association between RA and CVD, and perceived risk of CVD among individuals with RA.MethodsThree electronic databases (MEDLINE, EMBASE, and PubMed) were searched for English language articles between the years of 1990–2018. Search terms pertained to RA, CVD, knowledge, awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…The results from the present study indicate that patients with RA do not perceive the increased risk of CV disease associated with this condition. In keeping with our findings, it was suggested that patients with RA do not seem to be aware of this problem [ 14 ] and often have trouble perceiving their actual CV risk [ 15 , 16 ]. With respect to this, a recent systematic review [ 16 ] identified only six studies that assessed the degree of the perceived risk of CV disease development in patients with RA, comparing it with EULAR SCORE or with classic CV risk factors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results from the present study indicate that patients with RA do not perceive the increased risk of CV disease associated with this condition. In keeping with our findings, it was suggested that patients with RA do not seem to be aware of this problem [ 14 ] and often have trouble perceiving their actual CV risk [ 15 , 16 ]. With respect to this, a recent systematic review [ 16 ] identified only six studies that assessed the degree of the perceived risk of CV disease development in patients with RA, comparing it with EULAR SCORE or with classic CV risk factors.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, the number of patients included in these studies was close to 480 subjects with RA. This review concluded that patients with RA tend to misjudge their risk of developing CV disease, usually underestimating it [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the literature, as it has been reported that the levels of awareness and perceived risk of CVD is low in this patient population. 48 Gaps in care have also been reported when it comes to CV risk assessment. 7 12–14 This also highlights the importance of a systematic and proactive approach towards case finding by pharmacists—as many patients would not know to ask for CV risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The results were consistent with a systematic review which reported that a high proportion of RA patients were unaware of the association between RA and CVD risk. [ 19 ] Lack of awareness of healthcare providers regarding CVD prevention might result in RA patients’ low level of knowledge about RA-related CVD risk. [ 9 ] One study reported that while 100% of rheumatologists were aware of RA-related CVD risk, half of the general physicians were unaware of the RA-CVD link and acted as a barrier to the translation of knowledge to patients.…”
Section: Discussionmentioning
confidence: 99%